(untitled) (Revista Contexto & Educação, 2025)
This is a study on indigenous women in university, a mixture of struggles, challenges, articulation, resistance, dreams, utopia, and conquest, Kaingang and Guarani. This research is developed within the Graduate Program in Education at the Universidade Estadual do Centro-Oeste, aiming to identify the insertion and participation of women through their engagement with the university. The struggle of indigenous women occurs internally within their territories in the relation with their predominantly male leadership, within patriarchal family relations, and in the pursuit of higher education, both inside and outside the territories. This highlights the context and necessity for higher education and schooling for our people. The investigative problem clarifies that this territory has achieved advancements in job positions that previously did not exist, an aspect that requires higher education and has been challenged by access to public universities and, paradoxically, to private universities. Here, we intend to analyze the presence of indigenous women in higher education and their occupation of job positions within the territory. In order to produce data, we conducted a necessary bibliographic research in academic and scientific production. The central categories in the study include higher education, women, territory, and education, among others. In the fieldwork, we gather data on Kaingang and Guarani women in higher education, producing a qualitative and quantitative analysis framework. We note that there have been advances in these achievements, but the challenge of attaining higher education remains. It is emphasized that women still need to gain space in the management of their territories.